Transcriptome analysis reveals physiological responses in liver tissues of Epinephelus cyanopodus under acute hypoxic stress - Chen, Qiaoyi; Huang, Yukun; Yu, Zhiya; He, Wenjie; Hu, Xueqin; Wu, Jinhui; Cai, Tianguang; Cui, Yuhua; Gao, Along; Shu, Hu (Frontiers in Physiology, 2025)
Dissolved oxygen (DO) in aquatic ecosystems plays a pivotal role in fish farming, serving as a critical determinant for the sustainable development of aquaculture practices. When fish suffer hypoxic stress, they undergo a cascade of physiological adaptations. In this study, healthy E. cyanopodus were subjected to experimental treatments under normoxic (6.0 ± 0.05 mg/L) and hypoxic (1.6 ± 0.05 mg/L) conditions for 1 (H1), 3 (H3), 6 (H6), and 9 (H9) h to evaluate physiological responses. Liver RNA-seq analysis identified 6152 differentially expressed genes (DEGs) between the control group (H0) and the four hypoxia-treated groups (H1, H3, H6, H9). RNA-seq results indicated that hypoxia for 3–6 h was the key duration when significant physiological changes occurred in E. cyanopodus. KEGG enrichment analysis revealed significant involvement of these DEGs in key hypoxia-responsive pathways, including HIF-1 signaling, Glutathione metabolism, p53 signaling, PPAR signaling, and PI3K-Akt signaling pathways. These DEGs primarily played function in biological processes, including glycolysis/gluconeogenesis (aldob, hk, ldh-a, pparα, eno1, gpt), pyruvate metabolism (aldocb, ldh-a, fabp1), immune response (pnp, cxcl5, tnf-α, il1-β, il12-β), and apoptosis regulation (bax, bcl2, casp3). Their coordinated expression played a crucial role in mediating hypoxic adaptation of the liver and brain in E. cyanopodus. Three immune-related enzymes (AKP, ALT, AST), and two metabolic-related enzymes (GLU, LDH) were significantly expressed at 3 and 6 h. These results exactly proved that 3–6 h of hypoxic stress was the key period when E. cyanopodus experienced significant physiological changes. This study elucidated key physiological response changes underlying hypoxic stress in E. cyanopodus, which provided both theoretical framework for understanding hypoxic adaptation and practical insights for developing hypoxia-resistant breeding strategies.